Expedited Transition in the Wettability Response of Metal Meshes Structured by Femtosecond Laser Pulses for Oil-Water Separation - Khan, Sharjeel Ahmed; Ialyshev, Vadim; Kim, Vyacheslav V.; Iqbal, Mazhar; Al Harmi, Hamad; Boltaev, Ganjaboy S.; Ganeev, Rashid A.; Alnaser, Ali S. (Frontiers in Chemistry, 2020)
Oil-water separation by super-wetting and selective permeability of membranes for oil or water has great ecological and economic significance. We report on the transition of wettability response, from superhydrophilic underwater-superoleophobic to superhydrophobic-superoleophilic, by nanostructuring stainless steel and copper meshes using ultrashort femtosecond laser pulses. Our approach is environment-friendly, chemical free and, and efficient as it exploits the benefit of aging the processed samples in high vacuum environment. We optimized the laser scanning parameters, mesh pore size and ageing conditions to produce membrane exhibiting extraordinary separation efficiency of 98% for oil-water mixture. A variation in the water and oil contact angles for different meshes is presented as a function of laser scanning speed. Stainless steel meshes with 150 µm pore size and copper mesh with 100 µm pore size have demonstrated excellent wettability response for oil and water phases. Vacuum ageing causes rapid chemisorption of hydrocarbons on laser structured surface in the absence of water molecules, rapidly transforming the wetting state from superhydrophilic underwater-superoleophobic to superhydrophobic-superoleophilic state.